Trabalho e normatividade: uma análise ética dos discursos prescritivos do bom comportamento no trabalho - Silva, Daniel Rubens Santiago da (2014)
This is a theoretical study on the normativity of speech which guides the “good behavior” at work. Based on Gadamerian discussions, we start from the “initial prejudice”, which states the speech is subject to a critical ethics. The speech which regulate the ways of being, feeling, speaking and behaving at work are primarily seen in daily informative texts, such as newspapers and magazines. Such texts, presented in a sample way, work as triggers of the main question to be faced at work: is it possible to articulate a critique of ethical basis to these kinds of speech? How fair would they be? The resource to the critiques articulated in the psycho-sociological field is the starting point of this research. An argumentative articulated thought about the distance between the speeches that “prescribe autonomy” and the ones that “obligate participation”, for example, could be found. It is about a paradoxical speech. We could also notice the importance of the Human Capital Theory as the “self-management” technology and “control internalization”. We explore the speech contextualization in the large field of social transformations which the net contemporary society goes through and its inversions of public and private responsibilities. The normative speech of good behavior follows, or is followed by, the changings of the privatized society, which creates the psychologized subject. Lastly, we face the challenge of elaborating a critique which is eminently ethical. The notion of subjectivity as passivity before the Other brings Lévinas‟ ethical saying to the academic text. The Ethics‟ soil stands for the meeting facing the Other, only Other, needless of rules and laws. With the Third coming in, always according to Lévinas, it is articulated a justice which is the social equivalent of the ethical appeal about the me-Other parity. The ethical judgement is made with the Third. Then, the rules, laws and rights come into the scene. The prescriptive speech of “good behavior” at work shows itself as an unfair law without Alterity. The self-curving over itself at the self-management of Human Capital is shown as the closing to the Other. The initial prejudice which state these kinds of speech are passive of an ethical critique seems rightful.